Knowledge construction: the role of data mining tools - Ramos, Isabel (2003)
This paper seeks to integrate the process of knowledge discovery in databases in the wider context of the creation and sharing of organisational knowledge. The focus on the process of knowledge discovery has been mainly technological. The paper attempts to enrich that perspective by stressing the insights gained by integrating the knowledge discovery process into the social process of knowledge construction that makes KDD meaningful. In order to achieve this goal, a test case is presented. A component of the database of the Portuguese Army was used to test the PADRÃO system. This system integrates a set of databases and principles of qualitative spatial reasoning, which are implemented in the Clementine Data Mining system. The process and the results obtained are then discussed in order to stress the insights that emerge when the focus changes from technology to the social construction of knowledge.